2022
DOI: 10.3389/fcimb.2022.866259
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae Strains Isolated From a Single Pediatric Patient Display Distinct Phenotypes

Abstract: Streptococcus pneumoniae is the leading cause of bacterial paediatric meningitis after the neonatal period worldwide, but the bacterial factors and pathophysiology that drive pneumococcal meningitis are not fully understood. In this work, we have identified differences in raffinose utilization by S. pneumoniae isolates of identical serotype and sequence type from the blood and cerebrospinal fluid (CSF) of a single pediatric patient with meningitis. The blood isolate displayed defective raffinose metabolism, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 44 publications
(58 reference statements)
1
12
0
Order By: Relevance
“…Previously, we have shown that while the CSF clinical S. pneumoniae isolate (60CSF) is found in the ears of infected mice 24 h post intranasal infection, the blood isolate (60B) was unable to survive in this niche ( Agnew et al., 2022 ). To determine whether the observed different virulence phenotypes of 60B and 60CSF in mice could be mediated by rearrangements in the spnIII Type I restriction-modification (RM) system, the spnIII allele distribution was assessed from pneumococcal DNA extracted from the nasopharynx of intranasally infected animals.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we have shown that while the CSF clinical S. pneumoniae isolate (60CSF) is found in the ears of infected mice 24 h post intranasal infection, the blood isolate (60B) was unable to survive in this niche ( Agnew et al., 2022 ). To determine whether the observed different virulence phenotypes of 60B and 60CSF in mice could be mediated by rearrangements in the spnIII Type I restriction-modification (RM) system, the spnIII allele distribution was assessed from pneumococcal DNA extracted from the nasopharynx of intranasally infected animals.…”
Section: Resultsmentioning
confidence: 99%
“…The wildtype S. pneumoniae strains used in this study ( Table 1 ) were provided to us by the German National Reference Center for Streptococci (Aachen) ( Agnew et al., 2022 ). Pneumococci serotype 15C blood and CSF isolates (designated 60B and 60CSF, respectively) were isolated in 2015 from a child, aged 2, admitted to hospital with meningitis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations